PEMBERIAN EDUKASI KESIAPSIAGAAN BENCANA DI SD NEGERI 20 KOTO TANGAH TILATANG KAMANG - Kalpana Kartika; Lisa Fradisa Lisa Fradisa (COVIT (Community Service of Health), 2022)
SD Negeri 20 Koto Tangah is one of the basic vehicles for the nation's children to acquire knowledge and is an educational unit that produces generations of national scholars. Indonesia, as an archipelagic country whose islands are flanked by 3 tectonic plates, is therefore prone to natural disasters. The problem that is often faced today is the frequent occurrence of unexpected natural disasters such as earthquakes, floods, landslides and volcanic eruptions. The lack of knowledge, the absence of socialization or simulation in dealing with natural disasters, actually needs to get the main attention from various levels of society. Given the importance of early knowledge regarding disaster preparedness, the DIII Nursing Study Program as one of the study programs at the Faculty of Health, Perintis University also takes part in community service activities with the aim of providing early knowledge regarding disaster preparedness, through the theme "Providing Disaster Preparedness Education at 20 Koto Tangah Public Elementary School. The methods in this activity are providing education through counseling, watching video demonstrations and simulations. The results of the dedication show the great enthusiasm of students and the school community, seen from the earthquake simulation carried out by the school community, they succeeded in demonstrating good and correct evacuation actions, in accordance with the guidance and demonstrations that had been carried out. From these results it can be concluded that this educational activity can increase students' knowledge and awareness of the importance of early knowledge of disaster preparedness. Keywords: Education, Disaster Preparedness